Investigation of blowing and suction for turbulent flow control on airfoils - Fahland, Georg; Stroh, Alexander; Frohnapfel, Bettina; Atzori, Marco; Vinuesa, Ricardo; Schlatter, Philipp; Gatti, Davide (AIAA Journal, 2021)
An extensive parametric study of turbulent boundary-layer control on airfoils via uniform blowing or suction is presented. The control is applied on either the suction or pressure side of several four-digit NACA-series airfoils. The considered parameter variations include angle of attack, Reynolds number, control intensity, airfoil camber, and airfoil thickness. Two comprehensive metrics, designed to account for the additional energy required by the control, are introduced to evaluate the net aerodynamic performance enhancements. The study confirms previous findings for suction-side boundary-layer control and demonstrates the interesting potential of blowing on the pressure side under various conditions, which achieves a maximum total net drag saving of 14% within the considered parameter space. The broad parameter space covered by the presented Reynolds-average Navier–Stokes simulations allows for more general conclusions than previous studies and can thus provide guidelines for the design of future detailed experimental or numerical studies on similar boundary-layer control schemes.
CRIS-Team Scopus Importer:2023-03-21